Efektivitas Model Pembelajaran Problem-Based Learning dalam Meningkatkan Minat Belajar Peserta Didik pada Mata Pelajaran Informatika Kelas X Kuliner di SMK Negeri 9 Padang - Salma Maliki Ilmi (SAFE-Network, 2026)
This study aims to examine the effectiveness of the Problem-Based Learning method in increasing students' interest in learning informatics subjects in Class X Culinary at SMK Negeri 9 Padang. The method used in this study is classroom action research (CAR) with the Problem-Based Learning learning model. In its implementation, this classroom research action consists of four main steps, namely planning, action or action (acting), observation (observing), and reflection (reflecting). The research subjects were 36 students of class X Culinary 6. The results of the study indicate that the Problem Based Learning learning model in informatics subjects can increase students' interest in learning and which shows that in Cycle II with a score of 3010 with an average of 83.06 and the learning is included in the very good category. Thus, the application of the problem-based learning method has succeeded in increasing students' interest and ability in using Microsoft Excel and Word, as well as providing a good foundation for future learning development.